A comparative study of single layer extra mucosal versus conventional double layer anastomosis of intestines in elective and emergency laparotomy - Sai, K. Lohit; Sugumar, C. (International Surgery Journal, 2019)
Background: Gastrointestinal anastomosis has been a part of research since decades and is one of the key skills in surgeon’s armamentarium. This study compared the outcome of single layer anastomosis with double layer anastomosis. Methods: The study was designed as a prospective comparative study and 29 cases were included in the study during December 2016 to September 2017, who consented for being part of the study. Patients were alternatively allotted into the either group. Group A underwent single layer anastomosis and Group B underwent double layer anastomosis. Outcome parameters were analysed in the form of ‘duration required to perform anastomoses, ‘duration of hospital stay’ and ‘dnastomotic leak. Results: Mean duration required to perform anastomosis in Group A is 21.64±1.60 minutes and in Group B is 29.6±2.02 minutes. The difference between the mean duration required for anastomosis between the two groups were statistically significant (p<0.005). Mean duration of hospital stay in Group A was 12.35±1.72 days and Group B was 12±2.44 days (difference was statistically insignificant), 3 (10%) cases in Group A and 2 (6.8 %) cases in Group B developed anastomotic leak and the difference was statistically insignificant. Conclusions: Our study concluded that there is statistically significant difference between the single layer anastomosis and double layer anastomosis in terms of time taken to perform anastomosis, however there is no difference in postoperative anastomotic leak and duration of hospital stay.